Comparison of the Effectiveness of Cognitive and Metacognitive Strategies Training and Mindfulness on Academic Self-Regulation Components in Female High School Students - Hoodarsha, Fatemeh; Sepahmansour, Mozghan; Barzegar, Majid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
The objective of this study was to compare the effectiveness of cognitive and metacognitive strategy training and mindfulness training on the components of academic self-regulation—metacognition, cognition, and motivation—among female high school students. This applied, semi-experimental study employed a pre-test, post-test, and follow-up design with a control group. The statistical population consisted of female high school students in District 13 of Tehran during the 2024–2025 academic year. Using cluster sampling, 45 students with low academic self-regulation, hope, and buoyancy scores were selected and randomly assigned to three groups: cognitive and metacognitive strategies training (n = 15), mindfulness training (n = 15), and control (n = 15). Interventions consisted of eight weekly one-hour sessions based on McCombs’ cognitive-metacognitive training protocol and Kabat-Zinn’s mindfulness training protocol. Data were collected using the validated Academic Self-Regulation Questionnaire (Bouffard et al., 1995; Ghasemi & Fooladchang, 2011) at pre-test, post-test, and three-month follow-up. Data were analyzed using mixed ANOVA and Bonferroni post-hoc tests in SPSS v.22.Inferential results showed significant main effects of time and significant time-by-group interactions for all components of academic self-regulation (p < .0005). Cognitive and metacognitive strategy training produced the largest improvements in cognition and motivation, whereas mindfulness training was particularly effective in enhancing metacognitive awareness and demonstrated sustained improvements at follow-up. Bonferroni comparisons indicated that both intervention groups significantly outperformed the control group across all components, with cognitive and metacognitive strategies training showing stronger effects on motivation and cognition, while mindfulness training exhibited more durable effects on metacognition.